COMPOSITION OF AIR MICROBIOLOGY (International journal of medical sciences, 2025)
This scientific article extensively covers the structural structure of air microbiology, the processes of its enrichment with microorganisms distributed in the form of bioaerosols, and the mechanisms of preservation of microbiological factors in the atmospheric layer. The study analyzes in detail the natural sources, aerodynamic behavior, viability, and hygienic significance of bacteria, fungi, viruses, pollen particles, spores, actinomycetes, and organic residue aerosols. Also, the advantages and limitations of modern microbiological, physicochemical, and molecular biological methods used in the collection and identification of air samples are compared: impaction methods, sedimentation collection methods, volumetric aerosol sampling, qPCR, MALDI-TOF MS, and metagenomic sequencing methods. Ecological, meteorological, and anthropogenic factors (temperature, humidity, wind speed, industrial emissions, biotechnological production, and agricultural activities) affecting the concentration of microorganisms in the atmosphere are explained based on scientific literature and observations.